What Is Remedial Reading? A Descriptive Study - Allington, Richard ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
A study was conducted to provide preliminary information on the nature of remedial reading instruction. Specifically, the study examined the focus of remedial instruction and the relationships of this instruction to the classroom reading program. In addition, it gathered data on what instructional activities remedial students missed when they left their regular classrooms. Information was gathered through observation of remedial reading students both in their classroom reading instruction and in their remedial sessions. Students were from five different first through fourth grade classrooms in four different schools. Four of the five programs were organized around a "pull out" model wherein the students left the regular classroom for remedial instruction. The fifth was an in-class program in which instruction was delivered by a Chapter 1 aide. Results showed that while individual teachers used little instructional variety, they did use a wide range of materials. There was little evidence of the use of clear cut goals or of monitoring of student advancement toward goals, and teachers tended to use a single or small set of activities for all of their groups of students. Little congruence was found between instruction in regular classrooms and instruction in the remedial classes. Data also supported previous findings that Chapter 1 programs do not provide students with additional time for reading instruction. (FL)
ERIC Note: Paper presented at the Annual Meeting of the Colorado Council of the International Reading Association (18th, Denver, CO, February 7-9, 1985).
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Environment; Classroom Observation Techniques; Elementary Education; Program Content; Program Effectiveness; Program Evaluation; Reading Instruction; Reading Materials; Reading Research; Remedial Reading; Research Methodology; Teacher Effectiveness; Teacher Role; Teaching Methods; Education Consolidation Improvement Act Chapter 1; Reports, Research; Speeches/Meeting Papers